Empowering human communication to prevent viral spread / Siti Nur Fadzilah Abdullah and Efina Hamdan - Abdullah, Siti Nur Fadzilah; Hamdan, Efina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In an age where information spreads rapidly through various communication channels, it is crucial to empower human communication to prevent the spread of harmful viruses. While we often associate viruses with physical illnesses, the concept also applies metaphorically to the transmission of false information, negativity, and toxic behaviors through our interactions. First, let’s verify before sharing. In the digital age, misinformation and rumors can easily go viral, leading to panic, confusion, and a loss of trust. To prevent the spread of viral misinformation, it is essential to verify the accuracy of information before sharing it. Some simple practices such as cross-referencing multiple sources by consulting reputable sources and fact-checking websites to confirm the authenticity of the information. Other than that, consider the credibility of the source by evaluating the expertise and reliability of the source before sharing information. Next, let’s do some critical thinking by questioning information before accepting and forwarding it. Second, let’s promote positive communication. Avoiding negative communication can spread like a virus, leading to misunderstandings, conflicts, and damaged relationships. Empower human communication by focusing on positive engagement such as using constructive language by Choosing words that promote understanding, empathy, and cooperation. Moreover, encourage respectful discussions and diverse perspectives. Listen to others' opinions without immediately dismissing or attacking them. By practicing kindness and engaging in acts of kindness and support both online and offline. Encourage others to do the same, creating a ripple effect of positivity.